Vestibular anomalies and dysfunctions in children with inner ear malformations: A narrative review - Brotto, Davide; Ariano, Marzia; Sozzi, Mosè; Cenedese, Roberta; Muraro, Eva; Sorrentino, Flavia; Trevisi, Patrizia (Frontiers in Pediatrics, 2023)
About 20% of children with congenital hearing loss present malformations of the inner ear. In the past few years much has been understood about the morphology and function of the anterior part of the labyrinth, since hearing loss may have a dramatic effect on the overall development of a child. Nowadays, for most of them, a chance for hearing rehabilitation is available, making hearing loss a treatable condition. The anomalies range from the lack of development of the whole inner ear to specific anomalies of isolated structures. Despite the frequent concomitant involvement of the posterior part of the labyrinth, this part of the inner ear is frequently neglected while discussing its morphology and dysfunction. Even though vestibular and balance function/dysfunction may have a significant impact on the global development of children, very little is known about these specific disorders in patients with inner ear malformations. The aim of this review is to summarize the available literature about vestibular anomalies and dysfunctions in children with inner ear malformations, discussing what is currently known about the topic.